ANALISIS DAMPAK POLITIK UANG PADA PENYELENGGARAAN PEMERINTAHAN DESA: Kasus Pemilihan Kepala Desa Serentak di Kabupaten Bombana Tahun 2022 - La Ode Dedihasriadi (Halu Oleo University, 2023)
The election of village heads as an implementation of democracy aims to improve community welfare through public services. On February 20 2022, simultaneous village head elections were held in 109 villages in Bombana Regency, involving 22 sub-districts. This research uses a qualitative method with a purposive sampling technique, relying on primary data from interviews and observations, as well as secondary data from journals, books and other relevant sources In this democratic practice, it was revealed that almost all villages used money politics in various forms to win people's votes and sympathy. The implications of this money politics have an impact on the village government which is still relatively young, with new leadership less than a year old. These impacts include debts from candidates who are not elected, village development policies that are not in line with community needs, policies that are not in accordance with the principles of village governance, and the potential risk of corruption in public policy.